(untitled) (Ameghiniana, 2016)
The fossil genus Xylopteris was conceived for Corystospermales fronds presenting pinnate and basally bifurcate pinnae bearing narrow one-veined segments. Later, the possibility was proposed that some of its forms may include 2-3 bifurcated fronds with lobed pinnules and more complex venation. The fossil record attests to its exclusive occurrence in Middle-Upper Triassic Dicroidium floras from Gondwana. Among these, a significant portion of Xylopteris-related morphotypes was included either in the genus Dicroidium or as its subgenus. Such taxonomic placement was adopted in previous studies in Brazil. The new morphotypes herein described present an unsuspected diversity marked by well-preserved frond impressions accompanied by partially preserved Umkomasia strobili. They were identified in a limited exposure of lacustrine shales, at the top of the main fluvial succession of the Passo das Tropas Member, the lower lithostratigraphic unit of the Santa Maria Formation, in the Paraná Basin succession. Given the absence of anatomical structures, the proposed affinity with Xylopteris is based on the original characteristics assigned in the emended diagnosis and in comparisons with other Gondwana records. The described materials attest to the presence of widely distributed types, such as X. elongata, X. spinifolia, X. remotipinnulia and X. rigida as well as X. densifolia, which is restricted to South America and Africa. X. rotundipinnulia, a new generic combination and new species, is proposed for material from Southern Brazil and is comparable to that found in the Molteno beds. The obtained data expands the paleogeographic distribution of the genus and extends the age of the Dicroidium flora in Southern Brazil to the Carnian. Resumen. XYLOPTERIS (FRENGUELLI) STIPANICIC & BONETTI EN EL TRIÁSICO MEDIO-SUPERIOR (SANTA MARIA FORMATION) DE SUR DE BRASIL. El género fósil Xylopteris fue creado para hojas de Corystospermaceae con frondas bifurcadas en la base, de pinas simples, angostas, y pínulas con una sola vena. Posteriormente fue ahí incluida la posibilidad de que parte de sus frondas podrían tener un mayor número de bifurcaciones y pínulas lobuladas de más complexa venación. El registro fósil conocido atesta su exclusividad en las floras de Dicroidium del Triásico medio y superior del Gondwana. En estas asociaciones, una parte expresiva de sus morfotipos fueran incluidos en la diversidad de Dicroidium, o como su subgénero, postura igualmente adoptada en los estudios previos en Brasil. Los nuevos materiales acá descritos están compuestos por impresiones de frondas mejor preservadas y más diversificadas, asociadas a un registro de Umkomasia. Las impresiones de las frondas fueron identificadas en una nueva y restringida exposición de lutitas lacustres en la parte superior de los depósitos dominantemente fluviales del Miembro Passo das Tropas de la Formación Santa Maria, en cuenca Paraná. En la ausencia de estructuras anatómicas, la afinidad propuesta con Xylopteris está basada en los caracteres diagnósticos originales del género y su posterior enmienda, bien como, en su comparación con otros registros del Gondwana. Las nuevas formas descritas componen una asociación paleoflorística de morfotipos de amplia distribución en el Gondwana, como X. elongata, X. spinifolia, X. remotipinnulia and X. rigida, y tipos hasta ahora restringidos al sur de America y Africa, como X. densifolia. Una nueva combinación genérica y especie, X. rotundipinnulia es igualmente descrita, comparable a tipos identificados en las camadas de la Formacion Molteno. Los datos obtenidos permiten ampliar la distribución paleogeográfica del género y extender hasta el Carniano la edad de los depósitos con flora de Dicroidium en el sur de Brasil.